OPTIMASI KECEPATAN DAN LAMA PENGADUKAN TERHADAP UKURAN NANOPARTIKEL KITOSAN-EKSTRAK ETANOL 70% KULIT JERUK SIAM (Citrus nobilis L.var Microcarpa) - Wintari Taurina; Rafika Sari; Uray Cindy Hafinur; Sri Wahdaningsih; Isnindar Isnindar (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Siam citrus peel (Citrus nobilis L. var. Microcarpa) is a plant derived from Sambas Regency, West Kalimantan Province. Bioavailability of herbal active compounds can be enhanced by formulating extract into nanoparticle. The polymer used was chitosan with crosslinker Na-TPP. Stirring speed and stirring time play an important role to produce small particle size in forming nanoparticle using ionic gelation method. Enhancement of stirring speed and stirring time could reduce particle size. Nanoparticles were prepared using ionic gelation method by mixing Na-TPP, extract and chitosan (1:1:6) with varying the stirring speed 500 rpm, 1000 rpm, 1500 rpm and stirring time 1 hrs, 2 hrs, 3 hrs. The particle size of nanoparticle was found to be 85.3 nm at 1000 rpm of stirring speed and 3 hrs of stirring times, with polidispersity index 0.287, zeta potential +32.37 mV and entrapment efficiency 87.12 %.